Voces Mineras: Clarifying the future of artisanal and small-scale mining collaborations. Issue 1 (January 2020) - Smits, Kathleen M.; McDonald, Libby; Smith, Nicole M.; Gonzalez, Fernando; Lucena, Juan; Martinez, Gerardo; Restrepo, Oscar Jaime; Rosas, Silvia
Highlights: Existing programs have limited impact on building capacity to create sustainable ASGM practices. Co-design workshops are effective mechanisms for capacity building in ASGM communities. Main challenge of ASGM communities is disconnect between laws and regulations and realities of ASGM operations. Formalization hinges on developing an open and inclusive forum to allow artisanal and small-scale miners to articulate their needs. Miners proposed a simple process to formalization that includes all areas (mining, environment, health, safety, employee rights). Abstract: Using a creative capacity building (CCB) framework, co-design workshops among artisanal and small-scale gold miners, government officials, NGO representatives, and academics can provide an effective mechanism to identify pressing needs and desires of miners and operators towards formalization. As recently implemented in Peru, one of these workshops identified the need for a single forum (association) to allow artisanal and small-scale miners to represent their voice in front of government and large-scale mining operations and the need for a streamlined simple process for formalization that included mining, environment, health, safety, and employment considerations. A first step towards the single forum was taken with the creation of a social media outlet that allows participants to voice their concerns and share information. Future workshops are needed to cement the creation of the forum and provide specific recommendations for the streamlining of the formalization process.